PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium Ascalonicum L) PADA BERBAGAI KONSENTRASI PUPUK HAYATI SUPER BIOTA PLUS - Wa Ode Anti; La Sinaini (Jurnal Agrokompleks, 2020)
The purpose of this research is to know the influence of super biota biological fertilizer plus the growth and production of red onion plants (Allium asnomination) to know the concentration of super biota plus biological fertilizer that has the highest influence on growth and production of red onion plants (Allium asnomination). This research was conducted in Kasaka village of Kabawo subdistrict of Muna Regency in the month of June until August 2019. The experimental Design Used in this research is the group's random draft (RAK) One Facoradand the treatment that will be tried is the concentration of biological fertilizer. The results showed that the provision of various concentrations of super biota fertilizer plus the effect is very real to the plant height, number of leaves, number of saplings and production. Treat biota super fertilizer plus with a concentration of 12 cc/10 liters water gives the best growth and production of shallots with an average production reaches 5.13 t/ha.